A HEXAGONAL FRACTAL MICROSTRIP ANTENNA WITH ITS OPTIMIZATION FOR WIRELESS COMMUNICATIONS - Paras Chawla, Rohit Anand (International Journal of Advanced Science and Technology, 2020)
A brief discussion of a hexagonal microstrip antenna has been proposed in this paper in which the various iterations of a hexagonal shape are made. A hexagonal antenna has inherent property of a dual-band resonance. The bands may be translated to somewhat wider bands by introducing slots. This antenna may be simulated on HFSS Software. Further, the fabricated antenna may be compared with the simulated counterpart in terms of reflection coefficient, radiation pattern and peak gain to find the agreement between the results. Finally, the simulated antenna may be optimized in terms of any parameter such as bandwidth, reflection coefficient or gain and thereafter the optimized antenna may be fabricated again to confirm the simulated results. Such an optimized antenna may be utilized for the various microwave wireless applications.